Organizational Culture: An Empirical Study on Selected Garment Factories in Bangladesh - Alam, Akhund A. Shamsul (Asian Business Review, 2016)
The study is an attempt to identify and measure the perceived organizational culture in selected sample factories in the ready-made garments (RMG) sector. Based on the concept of the OCTAPACE framework – an acronym for ‘Openness’, ‘Confrontation’, ‘Trust’, ‘Authenticity’, ‘Pro-action’, ‘Autonomy’, ‘Collaboration’, and ‘Experimentation’, data were collected using OCTAPACE profile questionnaire developed by Dr. Udai Pareek. A total of 276 respondents, of which 70 are managers and 206 are workers were interviewed from 35 garment factories located in the Gazipur district of Bangladesh. Data was analyzed with Kolmogorov-Smirnov, Shapiro-Wilk and Mann-Whitney U tests as well as other suitable statistical tools. The results show that there is a significant difference in perception between managers and workers towards “Openness” and “Autonomy”. The study also identifies the strong, fairly strong and weak aspects of culture in terms of values and beliefs that prevail in the selected organizations. Finally, the degree and direction of correlation between the various elements of the OCTAPACE profile are measured for developing and maintaining a better organizational culture.JEL Classification Code: M 14
Keywords: Organizational Culture; OCTAPACE Profile; Values; Beliefs